2011
DOI: 10.1128/ec.05155-11
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Exported Type IV HSP40 Protein PfGECO in Plasmodium falciparum Gametocytes

Abstract: During Plasmodium falciparum infection, host red blood cell (RBC) remodeling is required for the parasite's survival. Such modifications are mediated by the export of parasite proteins into the RBC that alter the architecture of the RBC membrane and enable cytoadherence. It is probable that some exported proteins also play a protective role against the host defense response. This may be of particular importance for the gametocyte stage of the life cycle that is responsible for malaria transmission, since the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 94 publications
1
29
0
Order By: Relevance
“…2C). In agreement with these results, the putatively disrupted gene in IGM 2D3, pfl2550w, was knocked out independently and found to produce mature gametocytes (37). Thus, we believe that IGM 2D3 carries a second site mutation that accounts for the loss of gametocytogenesis.…”
Section: Discussionsupporting
confidence: 75%
“…2C). In agreement with these results, the putatively disrupted gene in IGM 2D3, pfl2550w, was knocked out independently and found to produce mature gametocytes (37). Thus, we believe that IGM 2D3 carries a second site mutation that accounts for the loss of gametocytogenesis.…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that these genes do have a specific role in some stage of gametocyte development. However, two of the genes identified in this study, pfgeco and P. falciparum LCCL domain-containing protein 2 (pfccp2; PF3D7_1455800/PF14_0532) have been successfully disrupted previously in other studies with no effect on gametocytogenesis, despite their expression in gametocytes 55,56 . The remaining genes identified thus require further validation to confirm whether they are in fact required for gametocyte development.…”
Section: Differential Display Analysismentioning
confidence: 87%
“…It is noteworthy that for other DnaJ family members, the converse is true; stimulating the ATPase of an Hsp70 is critical, but substrate binding is not (37). More recently, a group of type IV family members have been identified that possess a J domain without the highly conserved HPD consensus sequence (13,38,39), arguing that the importance of these two functions varies by the role of the specific DnaJ family member.…”
Section: Discussionmentioning
confidence: 99%